2023
DOI: 10.3390/su15118491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Women’s Leadership on Carbon Disclosure by the Top 100 Global Energy Leaders

Abstract: The energy sector is one of the main sources of carbon emissions and the most significant global polluter. Women’s concerns and the climate crisis were strongly associated when issues about climate change were first articulated in the United Nations Sustainable Development Goals stressing gender equality and climate mitigation actions have received very little attention in the last decade. Consequently, the primary issues raised by this study are the energy industry, and women and climate change. This study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 136 publications
(207 reference statements)
1
6
0
Order By: Relevance
“…The repository [23] comprehends three excel files which indicated that Table A, B and C where each of them are referring to data collected; and derived from the related research article [1] . The content of the files is summarized in Table 1 .…”
Section: Data Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…The repository [23] comprehends three excel files which indicated that Table A, B and C where each of them are referring to data collected; and derived from the related research article [1] . The content of the files is summarized in Table 1 .…”
Section: Data Descriptionmentioning
confidence: 99%
“… File name Name of the data in article File description CID Scores (Table A).xlsx Table A Binary and total CID scores for each company WDs Engagement (Table B).xlsx Table B Percentage of WDs’ engagement based on their classifications and percentage on the board EWDs Aggregated Score (Table C).xlsx Table C WDs engagement scores marked by aggregated score among the four dimensions of EWDs. CID aggregated score based on 90 item of CID index in research article [1] …”
Section: Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations